Silicon-nanoparticles doped biochar is more effective than biochar for mitigation of arsenic and salinity stress in Quinoa: Insight to human health risk assessment - Alsamadany, Hameed; Alharby, Hesham F.; Al-Zahrani, Hassan S.; Alzahrani, Yahya M.; Almaghamsi, Afaf A.; Abbas, Ghulam; Farooq, Muhammad Ansar (Frontiers in Plant Science, 2022)
The increasing soil contamination with arsenic (As), and salinity has become a menace for food security and human health. The current study investigates the comparative efficacy of plain biochar (BC), and silicon-nanoparticles doped biochar (SBC) for ameliorating the As and salinity-induced phytotoxicity in quinoa (Chenopodium quinoa Willd.) and associated human health risks. Quinoa was grown on normal, and saline soils (ECe 12.4 dS m-1) contaminated with As (0, 20 mg kg-1) and supplemented with 1% of BC or SBC. The results demonstrated that plant growth, grain yield, chlorophyll contents, and stomatal conductance of quinoa were decreased by 62%, 44%, 48% and 66%, respectively under the blended stress of As and salinity as compared to control. Contrary to this, addition of BC to As contaminated saline soil caused 31% and 25% increase in plant biomass and grain yield, however, these attributes were increased by 45% and 38% with the addition of SBC. The H2O2 and TBARS contents were enhanced by 5 and 10-fold, respectively under the combined stress of As and salinity. The SBC proved to be more efficient than BC in decreasing oxidative stress through overexpressing of antioxidant enzymes. The activities of superoxide dismutase, peroxidase and catalase were enhanced by 5.4, 4.6 and 11-fold with the addition of SBC in As contaminated saline soil. Grain contamination of As revealed both the non-carcinogenic and carcinogenic risks to human health, however, these effects were minimized with the addition of SBC. Grain As accumulation was deceased by 65-fold and 25-fold, respectively for BC and SBC addition to As contaminated saline soil. The addition of SBC to saline soils contaminated with As for quinoa cultivation is an effective approach for decreasing the food chain contamination and improved food security. However, more research is warranted for the field evaluation of effectiveness of SBC in abating As uptake in other food crops cultivated on As polluted normal and salt affected soils.